The Symbolic Architecture and Meaning of the Church of GKI Jahja Sasari, Biak Numfor Regency, Papua - Deasy Widyastomo; Wika Matana Nion (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The architecture of the Church of GKI Jahja Sasari building displays symbols and ornaments taken from the Bible, which tell of the presence of the Trinity of God on earth as an expression of faith and a sacred and majestic religious atmosphere. Symbols in the form of two-dimensional and three-dimensional objects are arranged to beautify the church and have a spiritual meaning as a great place of worship. Symbols and symbolic ornaments are placed inside the church (interior) and outside the church (exterior), functioning to support the church atmosphere visually and to help the appreciation of faith aesthetically, psychologically, and religiously. The Church GKI Jahja Sasari in the Aimando Padaido village islands of Biak Numfor Regency is a Protestant Christian Church characterized by traditional and modern architecture, which is equipped with symbols and ornaments on the interior and exterior of the church which tries to maintain the ornaments and symbols of the church built by their ancestors in 1962. The ornaments built by the ancestors were retained in the new church building, reflecting the presence of biblical symbols in the modern architectural principles underlying the church design. The research problem is the existence of symbols and symbolic ornaments in the Church of GKI Jahja Sasari, which combines traditional and modern architecture and presents aesthetic, psychological, and religious aspects. The study was carried out by analyzing secondary data (photos and text), literature studies, and old church buildings formed by the ancestors of the Biak indigenous people, then comparing them with the basic guidelines for Protestant Christian church architecture and the principles of modern architecture. As a result, the Church of GKI Jahja Sasari combines traditional and modern architecture with an expression of an approach to the geography of the Pacific coast and the culture of the Biak people. The presence of the cross and dove symbols visually marks the GKI Protestant Christian church’s presence with the Trinity God’s presence; the interior symbolic ornaments strengthen its uniqueness as a sacred (religious) space. The shape and number of windows symbolize the number of indigenous peoples who inhabit the Aimando Padaido islands with a modern architectural style and provide space for symbols and symbolic ornaments. There is a mixture of modern traditional architecture with the symbolism of the church as a holy and sacred building of worship.